Battery plug-in electric vehicle : completing the chassis build and related sub-assemblies - Muhammad Nasrun Roslan (2016)
This Final Year Project report serves to document as detailed as possible the further work on the NTU battery Electric Vehicle (BEV) or Nanyang Venture VII which is into its 5th year. The author’s role in the student team is to fabricate the chassis parts on the first half of the project duration. After which, major components such as parking brake, reinforcement bumper, seats and seat belts are integrated by the author. In the initial phase, the author reviewed previous team work to determine what they have done and how the work will be continued. The author also has to undergo training on machining skills and manufacturing processes and of the various components to better understand how to integrate the parts. Only parts and components that the author fabricate for the chassis will be mentioned with emphasis on how it was completed. Assembly of the sub-frames, gearbox and the motor will be briefly mentioned which was a team effort. A list of future work will also be discussed.